AESTHETIC VALUE OF RE-USE WASTE MATERIALS AS A PANACEA FOR ENVIRONMENTAL PROTECTION (An Appraisal of Oligbinde's Creative Works) - Oligbinde, S.R,; Adesanya, C.O,; Oyeniyi E, O, (EPRA International Journal of Research and Development (IJRD), 2022)
Discarded plastic and bottle tops are unwanted and seen as unusable materials that the initial user has no further use for or no longer considers of any significant value to retain. They are considered waste, thus, discarded after primary use. The indiscriminate disposal of such waste amounts to an alarming volume of them, however, wastes can be managed through recycling, repurposing and if well managed, a man stands at a vantage point economically, socially, and more importantly aesthetically – which affects our health on short and long terms. This paper examines the plastic sculptures of Oligbinde Rotimi with the concept of turning plastic waste into objects of aesthetic made from discarded plastics that are purposively selected for formal and contextual analysis. These works were produced as a source of inspiration for others to gainfully redeploy any plastic they see within their enabling environment to lay their hands on and thereby save the planet committed to us. Photographs of works are taken and the procedures involved in executing the works were highlighted.